Comprehensive Analysis of Codon Usage Bias in Seven Epichloë Species and Their Peramine-Coding Genes - Song, Hui; Liu, Jing; Song, Qiuyan; Zhang, Qingping; Tian, Pei; Nan, Zhibiao (Frontiers in Microbiology, 2017)
Codon usage bias plays an important role in shaping genomes and genes in unicellular species and multicellular species. Here, we first analyzed codon usage bias in seven Epichloë species and their peramine-coding genes. Our results showed that both natural selection and mutation pressure played a role in forming codon usage bias in seven Epichloë species. All seven Epichloë species contained a peramine-coding gene cluster. Interestingly, codon usage bias of peramine-coding genes were not affected by natural selection or mutation pressure. There were 13 codons more frequently found in Epichloë genome sequences, peramine-coding gene clusters and orthologous peramine-coding genes, all of which had a bias to end with a C nucleotide. In the seven genomes analyzed, codon usage was biased in highly expressed coding sequences (CDSs) with shorter length and higher GC content. Genes in the peramine-coding gene cluster had higher GC content at the third nucleotide position of the codon, and highly expressed genes had higher GC content at the second position. In orthologous peramine-coding CDSs, high expression level was not significantly correlated with CDS length and GC content. Analysis of selection pressure identified that the genes orthologous to peramine genes were under purifying selection. There were no differences in codon usage bias and selection pressure between peramine product genes and non-functional peramine product genes. Our results provide insights into understanding codon evolution in Epichloë species.